(untitled) (Actual Problems of Psychology in Educational Institutions, 2021)
The article presents the external and internal factors contributing to the occurrence of the phenomenon of procrastination; the survey reveals the essence of the procrastination concept as a complex phenomenon; its varieties and classifications; it is also shown the main types of procrastination; and it is presented the list of tests made by known researchers concerning problems of the general and academic procrastination; the article analyzes the means of preventing procrastination based on self-regulatory skills proposed by various scientists; the study shows several newest effective methods of struggling procrastination processes; the paper clarifies the ways of prevention and means of overcoming in order to stop the processes of inhibition of the qualitative personal development.